The Influence of Organizational Justice and Ethical Leadership on the Innovation Behavior of Employees of PT Bukit Asam TBK - Masrukhin, Muhamad Agus; Indiyati, Dian (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The decline in employee participation in the Bukit Asam Innovation Award (BAIA) at PT Bukit Asam Tbk (PTBA) signals the need to explore factors influencing innovation behavior. This study focuses on the role of organizational justice and ethical leadership in shaping employees’ innovative actions. A quantitative method was employed, using descriptive and causal approaches. Data were gathered through structured questionnaires distributed to 325 employees selected via stratified random sampling. Structural Equation Modeling based on Partial Least Squares (PLS-SEM) using SmartPLS 4.0 was applied to analyze the data. Descriptive analysis shows that organizational justice is perceived as “very high,” ethical leadership as “very good,” and innovation behavior as “good.” The hypothesis test results confirm that both organizational justice and ethical leadership significantly and positively influence innovation behavior, with a combined contribution of 72.1%. This demonstrates that a fair organizational climate and ethical leadership practices are essential drivers of innovation. The research provides practical implications for PTBA, especially in evaluating and enhancing policies related to fairness and leadership to foster a more innovative organizational culture. Moreover, the study contributes to the literature by empirically supporting the relationship between organizational justice, ethical leadership, and innovation behavior. It is recommended that future research explore similar variables in different company or industry contexts to validate and expand the findings.